2021
DOI: 10.1161/circheartfailure.120.007937
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Outcomes Following Cardiogenic Shock Requiring Acute Mechanical Circulatory Support

Abstract: Background: The association of obesity on outcomes in patients with cardiogenic shock requiring acute mechanical circulatory support has not been thoroughly investigated. Methods: We evaluated the National Readmission Database for adults with either acute myocardial infarction or heart failure complicated by cardiogenic shock requiring acute mechanical circulatory support between January 2016 and November 2017. Exposure was assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 29 publications
0
39
1
Order By: Relevance
“…In their multivariate‐adjusted model, mortality was 37% lower in the men who were obese, but obesity did not affect mortality in women, with evidence of significant interaction ( P value for the association between BMI and sex 0.023). The results in the present study by Kwon et al 15 appear to differ from the recent publications, 13 , 14 which did not find an obesity paradox in CS. There are significant methodological differences between prior evaluations and the Kwon study that may shed light on these observations.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In their multivariate‐adjusted model, mortality was 37% lower in the men who were obese, but obesity did not affect mortality in women, with evidence of significant interaction ( P value for the association between BMI and sex 0.023). The results in the present study by Kwon et al 15 appear to differ from the recent publications, 13 , 14 which did not find an obesity paradox in CS. There are significant methodological differences between prior evaluations and the Kwon study that may shed light on these observations.…”
contrasting
confidence: 99%
“… 11 , 12 Similarly, an obesity paradox has not been demonstrated in cardiogenic shock. Recently, Sreenivasan and colleagues 13 did not find an obesity paradox in a large US population of cardiogenic shock (CS) compared with those who were nonobese, and moderate and severe obesity had progressively higher mortality. 13 , 14 …”
mentioning
confidence: 99%
“…Therefore, extrapolation of the results to a Western population, where a different definition for obesity is used, may be limited. Because the extremely obese in our study had the same BMI as obese individuals in Western countries, and worse outcomes were reported in the extremely obese group in previous studies, 14 , 30 , 31 , 32 further analysis with this group would have helped to better understand the effects of obesity; however, the number of patients in the extremely obese group was too small to have any statistical power (n=50). However, in a cubic spline curve drawn with BMI as a continuous variable, men with BMIs >30.0 kg/m 2 still showed significant lower ORs for mortality, so this might at least give a clue of what might have occurred had our population had a sufficient number of patients with higher BMI––although this is mere speculation and should be investigated in future larger studies.…”
Section: Discussionmentioning
confidence: 95%
“…The principal determinant of obesity and other cardiometabolic diseases is lifestyle, of which food habit is a main component ( 15 ). In our study, we found that the prevalence of obesity among FIS adults was higher compared to FS adults.…”
Section: Discussionmentioning
confidence: 99%